Analysis for FRP strenghtened RC walls subjected to blast loading - Omar Abdul Razak (2016)
Presently, the need to increase the resistance of existing structures against blasts had increased, especially for those not designed to resist any explosion. This is because of the rising threat of terrorists’ attacks or sabotage, making them very vulnerable. Thus, more experimental and finite element research had been undertaken to study fibre reinforced polymers (FRP) as a strengthening or retrofitting material for blast protection of concrete structures. This report reviews the experimental research findings from available literature on the effectiveness of having FRP retrofit on existing walls (or slabs) against blasts. Three main areas of improvement will be studied; displacement/deformation, post blast damage and residual strength as well as flexural/shear capacity. The findings showed that having FRP as an external reinforcement or retrofit has sufficient benefits, in terms of reducing deformation and post blast damage, increasing the post blast residual strength and improving flexural as well as shear capacity. These improvements may then be applied in design, serviceability or repair of new and existing targeted structures for protection. In addition, installation procedures of common FRP systems currently available will be mentioned. However, currently there is a lack of a complete and comprehensive design guide for FRP systems used specifically for blast protection. Thus, what could be done is to merge the available different design guides for general FRP strengthening of RC structures and that of blast protection to find a feasible and workable solution.